2008
DOI: 10.5009/gnl.2008.2.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Sulfur Compounds as a Predictor for Esophagogastroduodenal Mucosal Injury

Abstract: Background/Aims: Halitosis is a symptom that bothers patients more socially than medically and its pathogenic mechanisms are unclear and treatment armamenterium is limited. Clinicians generally ignored active interventions. Since halitosis is closely associated with volatile sulfur compounds (VSCs), we used a Halimeter and gas chromatography to measure VSCs in patients with Helicobacter-pylori (H. pylori)-associated gastric diseases. Methods: We categorized 72 patients with H. pylori infection into two groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…Data from a previous study [23] suggested that breath VSC levels indicated the presence of erosive or mucosal injury in patients with functional dyspepsia. Thus, to determine the effects of H. pylori infection on VSC levels, we recruited 55 subjects with functional dyspepsia.…”
Section: H Pylori Infection and Vsc Levelsmentioning
confidence: 93%
“…Data from a previous study [23] suggested that breath VSC levels indicated the presence of erosive or mucosal injury in patients with functional dyspepsia. Thus, to determine the effects of H. pylori infection on VSC levels, we recruited 55 subjects with functional dyspepsia.…”
Section: H Pylori Infection and Vsc Levelsmentioning
confidence: 93%
“…As result, we speculated that halitosis could be the extraesophageal manifestation of ERD, but it might be the results of the presence of esophageal mucosal damages, similar result with our previous publication. 13 Therefore, we assert that minimal change lesion could be a part of ERD rather than NERD in its nature determined by the nature of Halimeter ppb reflecting the presence of mucosal injury. The mean ppb levels in NERD patients with hiatal hernia were 191.11±32.55 and the levels of ppb in NERD without hiatal hernia were 121.59±13.69, of which statistical difference was significant (p=0.029).…”
Section: Resultsmentioning
confidence: 80%
“…11,12 In a previous study, we measured VSCs among the patients who had injured gastric mucosa, checking VSC levels by Halimeter of oral air or gas chromatography of gastric juice, and reached to the conclusion that halitosis might have significant correlation with mucosal damage after Helicobacter pylori (H. pylori) infection. 13 The core points we have found from this previous study was that the injured esophagogastroduodenal mucosa have potential of generating VSCs supported with the fact that there was statistical difference in VSC levels between eroded esophageal mucosa and noneroded mucosa. Additional report was followed that Korea red ginseng could relieve halitosis through their anti-inflammatory and cytoprotective actions in patients with H. pylori-infected gastritis.…”
Section: Introductionmentioning
confidence: 64%
“…5,14 However, other studies have proposed a significant relationship between halitosis and GERD (Table 4). [16][17][18][19]29 16,29 In these studies, the erosive reflux disease group had higher VSC values than the NERD group. However, these studies lacked a true control group, such as healthy subjects.…”
Section: Discussionmentioning
confidence: 78%